Inovação Global de Subsidiárias Estrangeiras Localizadas em Mercados Emergentes - Sidney Costa; Felipe Mendes Borini; Marcos Amatucci (RAC: Revista de Administração Contemporânea, 2013)
The purpose of this paper is to show that global innovation in foreign subsidiaries located in emerging markets depends directly on the international competitive context and indirectly on the national competitive context. This requires subsidiaries participate in networks external to the host country to benefit from a domestic competitive context. For this reason, the article uses foreign subsidiaries installed in Brazil as the object of research, as a representative sample of subsidiaries located in emerging markets. Structural equation modeling was applied to a survey conducted with subsidiaries in Brazil to test proposed hypotheses. The results show that foreign subsidiaries that carry out activities of global innovation while located in emerging markets use differentiated strategies to access resources in the external environment. In order to benefit from the host country’s national competitive benefits, subsidiaries need to get involved in technical networks as a means of learning to operate in an emerging market and overcome domestic market challenges. Subsidiaries integrated in global supply chains make direct use of the international competitive contexts located in developed countries.